2018
DOI: 10.1002/ijc.31762
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lymphocytic leukemia cells increase neutrophils survival and promote their differentiation into CD16highCD62Ldim immunosuppressive subset

Abstract: Reprogramming of neutrophils by malignant cells is well-described for many types of solid tumors, but data remain scarce for hematological diseases. Chronic lymphocytic leukemia (CLL) is characterized for a deep immune dysregulation mediated by leukemic cells that compromises patient's outcome. Murine models of CLL highlight the relevance of myeloid cells as tumor-driven reprogramming targets. In our study, we evaluated neutrophil reprogramming by CLL cells. We first show that the proportion of the CD16 CD62L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…Using a nucleofection plasmid transfection protocol, the transfection efficiency in neutrophils is low (~5%), when evaluated two hours post-transfection ( 58 ). Researchers have attempted to overcome this limitation by introducing granulocyte-macrophage colony-stimulating factor (GM-CSF) in the culture medium ( 59 ), while use of the leukemia cell line HL-60 as an alternative model ( 60 ) or direct electroporation of neutrophils ( 61 ) represent additional approaches to overcome this problem. The limitation for HL-60 cells is that they cannot mimic all aspects of neutrophil biology, and the conclusion from our in vitro experiment is that HL-60 cells cannot fully mimic the in vivo environments.…”
Section: Discussionmentioning
confidence: 99%
“…Using a nucleofection plasmid transfection protocol, the transfection efficiency in neutrophils is low (~5%), when evaluated two hours post-transfection ( 58 ). Researchers have attempted to overcome this limitation by introducing granulocyte-macrophage colony-stimulating factor (GM-CSF) in the culture medium ( 59 ), while use of the leukemia cell line HL-60 as an alternative model ( 60 ) or direct electroporation of neutrophils ( 61 ) represent additional approaches to overcome this problem. The limitation for HL-60 cells is that they cannot mimic all aspects of neutrophil biology, and the conclusion from our in vitro experiment is that HL-60 cells cannot fully mimic the in vivo environments.…”
Section: Discussionmentioning
confidence: 99%
“…CD62L dim neutrophils are thought to be an independent subset due to their unique transcriptional properties in response to acute inflammation 36 , while another study illustrated their poor antimicrobial activity 37 . However, scholars in different fields have reported that CD62L dim neutrophils present as an immunosuppressive subset that promotes disease progression, especially in chronic lymphocytic leukemia 22 , 38 , 39 . In contrast, the literature suggests that CD62L dim neutrophils are associated with improved survival in patients with head and neck squamous cell carcinoma (HNSCC) 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity of neutrophils has been well shown, with identified cell types such as the tumor-killing N1 neutrophils, tumor-promoting N2 neutrophils, low-density neutrophils (LDNs) and high-density neutrophils (HDNs) 20 , 21 . In addition, some studies have shown that tumor cells in chronic lymphocytic leukemia promote neutrophil differentiation into the CD62L dim phenotype, which exerts immunosuppressive functions 22 . However, the influence of these processes on the changes and effects on tumor metastases have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In another study of colorectal cancer patients receiving any form of cancer therapy, the expression of CD38 was increased in circulating neutrophils relative to untreated patients and healthy donors [114]. In chronic lymphocytic leukemia, leukemic lymphocytes promoted the ex vivo differentiation of neutrophils into a more immunosuppressive population, characterized as CD16 high CD62L dim , compared with neutrophils that were not exposed to these cells or their conditioned media [115]. Finally, two distinct neutrophil populations of CD13 high and CD13 low neutrophils, that are present both in blood and tumor tissues, were described in patients with pancreatic ductal adenocarcinoma (PDAC) [116], whereas two different circulating neutrophil populations were found based on the differential expression of immunoglobulin-like transcript 3 (ILT3)high and lowin NSCLC patients [117].…”
Section: Neutrophil Diversity and Heterogeneity In Cancermentioning
confidence: 97%